Analytical performance of the zero padded multibands OFDM under UWB environments - Anas, N. M. (IEEE Explorer, 2011)
This paper presents the performance analysis of multiband OFDM technique for the UWB system under indoor environment using Zero padded prefix which has been suggested in ECMA-368 standard as to avoid power back off at the transmitter. A modified Saleh-Valenzuela channel modeling is considered as a realistic multipath indoor characteristic with four channel model: CM1, CM2, CM3 and CM4. These channel models are distinguished by cluster structure of the receiving path and its respective cluster and ray within cluster decay factors rate. Rayleigh fading is used as an upper bound limit of the analytical performance of UWB system.